Tagging polyketides/non-ribosomal peptides with a clickable functionality and applications - Zhu, Xuejun; Zhang, Wenjun (Frontiers in Chemistry, 2015)
Bioorthogonal chemistry has recently emerged to be one of the most powerful tools in drug discovery and chemical biology. The exploration of it has successfully advanced the field of natural product research. In this Perspective, we survey current strategies for the installation of chemical handles into the molecular scaffolds of several major classes of natural products, including polyketides, non-ribosomal peptides, and their hybrids. By tagging these natural products with chemical handles and coupling them with subsequent bioorthogonal reactions, researchers have visualized and studied the mode of action of natural products, as well as synthesized derivatives with better pharmaceutical properties. We conclude this Perspective by considering two questions: Is there a general way to synthesize tagged polyketides/non-ribosomal peptides? Does natural product labeling have a broader impact in the field of natural product research beyond current known applications?